Application of Data Mining Techniques in the Analysis of Indoor Hygrothermal Conditions - Ramos, Nuno M.M; Delgado, João M.P.Q; Almeida, Ricardo M.S.F; Simões, Maria L.; Manuel, Sofia (SpringerBriefs in Applied Sciences and Technology, 2016)
The main benefit of the book is that it explores available methodologies for both conducting in-situ measurements and adequately exploring the results, based on a case study that illustrates the benefits and difficulties of concurrent methodologies. The case study corresponds to a set of 25 social housing dwellings where an extensive in situ measurement campaign was conducted. The dwellings are located in the same quarter of a city. Measurements included indoor temperature and relative humidity, with continuous log in different rooms of each dwelling, blower-door tests and complete outdoor conditions provided by a nearby weather station. The book includes a variety of scientific and engineering disciplines, such as building physics, probability and statistics and civil engineering. It presents a synthesis of the current state of knowledge for benefit of professional engineers and scientists.